Comparing Volume Loss in Neuroanatomical Regions of Emotion versus Regions of Cognition in Healthy Aging - Pressman, Peter S. (PLoS One, 2016)
Many emotional functions are relatively preserved in aging despite declines in several cognitive domains and physical health. High levels of happiness exist even among centenarians. To address the hypothesis of whether preservation of emotional function in healthy aging may relate to different rates of age-related volume loss across brain structures, we performed two volumetric analyses on structural magnetic resonance neuroimaging of a group of healthy aging research participants using Freesurfer version 5.1. Volumes selected as supporting cognition included bilateral midfrontal and lateral frontal gyri, lateral parietal and temporal cortex, and medial temporal lobes. Volumes supporting emotion included bilateral amygdala, rostral anterior cingulate, insula, orbitofrontal cortex, and nucleus accumbens. A cross-sectional analysis was performed using structural MRI scans from 258 subjects. We found no difference in proportional change between groups. A longitudinal mixed effects model was used to compare regional changes over time in a subset of 84 subjects. Again, there was no difference in proportional change over time. While our results suggest that aging does not collectively target cognitive brain regions more than emotional regions, subgroup analysis suggests relative preservation of the anterior cingulate cortex, with greater volume loss in the nucleus accumbens. Implications of these relative rates of age-related volume loss in healthy aging are discussed and merit further research.